Engineering the collapse of lifetime distribution of nitrogen-vacancy centers in nanodiamonds - Li, Hao (2021)
We demonstrate experimentally that the distribution of the decay rates of nitrogen-vacancy centers in diamond becomes narrower by over five times for nanodiamonds embedded in thin chalcogenide films.